Idle performance of a hydrogen rotary engine at different excess air ratios. (25th January 2018) - Su, Teng; Ji, Changwei; Wang, Shuofeng; Shi, Lei; Yang, Jinxin; Cong, Xiaoyu
Abstract: Rotary engine has flat chamber and longs for fuel with high flame speed and small quenching distance. Hydrogen has many excellent characteristics that are suitable for the rotary engine. In this paper, the performance of a rotary engine fueled with pure hydrogen at different excess air ratios was experimentally investigated. The investigation was carried out on a single-rotor hydrogen-fueled rotary engine equipped with port fuel injection system. An online electronic control module was used to govern the hydrogen injection duration and excess air ratio. In this study, the engine was operating at the idle speed of 3000 rpm and different excess air ratios varied from 0.993 to 1.283. The test results demonstrated that the fuel energy flow rate of the hydrogen rotary engine and engine stability were reduced with the increase of excess air ratio. When the excess air ratio increased from 0.993 to 1.283, the hydrogen energy flow rate was decreased from 14.91 to 11.55 MJ/h. Both the flame development and propagation periods were increased with excess air ratio. CO emission was negligible, but HC, CO2 and NOx emissions were still detected due to the evaporation and possible burning of the lubrication-used gasoline, and oxidation reaction of nitrogen of the intake air. Highlights: The idle performance of a H2 rotary engine at various λ s was studied. Ef was decreased when λ was enlarged. CA0-10 and CA10-90 were prolonged with the increase of λ . HC, CO and NOx were reduced when λ was increased.